Peran BKM Masjid Nurul Amal Dalam Membina Aqidah Masyarakat di Desa Ponjian Pegagan Julu X Kecamatan Sumbul Kabupeten Dairi - Sania Mariana Bancin (Islam & Contemporary Issues, 2021)
This study examines the role of the Nurul Amal Mosque BKM in Fostering Community Aqidah in Ponjian Pegagan Julu X Village, Sumbul District, Dairi Regency. The more humans deepen the Qur'an, the more it will be seen that the position of faith in Islam is the main thing and must be proven by real behavior. It is even explained that one of the signs of the strength of one's creed is when it is mentioned about His greatness and power. In today's modern and sophisticated society, it is clear that society is changing more and more. Moreover, the current conditions that require humans to fulfill their daily needs are often negligent with the rules and regulations of religion so that they come out of the creed and religious law and violate the norms that apply in society.Islamic aqeedah is very decisive for a Muslim, because in this system of religious theology it is believed that attitudes, actions, and changes that occur in a person's behavior and activities are strongly influenced by the aqidah he adheres to. The purpose of this research is to find out the activities carried out by the BKM management in fostering the community's aqidah, to find out the worship activities of the Nurul amal Ponjian mosque and to find out the role of BKM in fostering the community's aqidah. The methodology used in this research is through field research with a qualitative approach, data collection techniques are processed from the results of direct observations with resource persons and documentation.